Structuration of lignin-graphene oxide based carbon materials through liquid crystallinity. (August 2019) - Föllmer, Marie; Jestin, Simon; Neri, Wilfrid; Derré, Alain; Bentaleb, Ahmed; Mercader, Célia; Poulin, Philippe
Abstract: This paper presents the approach of combining lignin with graphene oxide (GO) flakes in order to introduce a higher structuration inside amorphous carbon materials. Both the phase behavior of lignin-GO solutions and the properties of lignin-GO films are investigated in a first approach. A clear orientation within lignin-based solutions is obtained through the formation of a nematic liquid crystalline GO phase. The impact of the GO flakes on the lignin-GO films after their carbonization is demonstrated via scanning electron microscopy and X-ray diffraction measurements. With increasing GO content inside the composite films, a layer-like morphology and graphitic structures of higher crystallinity are found. The electrical conductivity of the films gradually increases as well. Furthermore, we demonstrate successful spinning trials of lignin-GO solutions into composite fibers by means of coagulation. An increased electrical conductivity of the obtained fibers depending on the GO concentration indicates an increase in crystallinity. The structuration of lignin-based carbon materials may represent an important approach towards bio-based carbon fibers with improved mechanical and electrical properties. Graphical abstract: Image 1